Lyricism: A Free Category or a Relevant Concept in Domestic Literary Criticism? - Shevchuk, Yuliya V. (Studia litterarum, 2024)
“Lyrical” / “lyricism” / “lyrical principle” is used as an independent term, in combination with the object of study (prose, cycle, poem) or an adjacent phenomenon (“lyro-epic”) quite widely. Theoretical comprehension and justification of the term “lyricism” remains an undeveloped category in philology. Reflections of domestic researchers on lyrics as a literary genre, practical developments in the analysis of literary works, and the critical development of the problem by the poets themselves allow us to draw some generalizations and conclusions. The article primarily addresses the content and boundaries of the concept of lyrical, which appears as the complex ideological-emotional unity of the author, character, and reader in lyrics and works of synthetic forms. The interaction of subjects (the author and the “other”) occurs in an atmosphere of trusting emotionality of a close situation of confession. The compassionate reader finds himself “inside” the lyrical event, and his dialogue with the author and character has a cathartic outcome. Forms of lyricism in synchrony encapsulate typical traits. Still, to a large extent, they depend on the sense of matter in each particular author, and therefore, in recognized lyricists, they appear as innovations within the traditional literary system. By its nature, lyricism is an intersubject phenomenon, so understanding its forms that convey the general in the spiritual system of generations and masses of people can be promising in diachronia.